2018
DOI: 10.4102/phcfm.v10i1.1582
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of neonatal jaundice and risk factors in healthy term neonates at National District Hospital in Bloemfontein

Abstract: BackgroundNeonatal jaundice affects one in two infants globally. The jaundice is the result of an accumulation of bilirubin as foetal haemoglobin is metabolised by the immature liver. High serum levels of bilirubin result in lethargy, poor feeding and kernicterus of the infant.AimThe main aim of this article was to determine the prevalence of neonatal jaundice and secondly to explore its risk factors in healthy term neonates.SettingMaternity ward, National District Hospital, Bloemfontein, South Africa.MethodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 13 publications
(27 reference statements)
3
70
3
6
Order By: Relevance
“…The term ‘jaundice’ is used to describe the yellow-orange discolouration of the skin and conjunctiva due to excessive bilirubin in the skin and mucous membranes 1 2. It is not a disease, but a symptom or sign of a disease 3. Jaundice (hyperbilirubinaemia), although a common benign occurrence in the first week of life, can sometimes progress to critical levels 4.…”
Section: Introductionmentioning
confidence: 99%
“…The term ‘jaundice’ is used to describe the yellow-orange discolouration of the skin and conjunctiva due to excessive bilirubin in the skin and mucous membranes 1 2. It is not a disease, but a symptom or sign of a disease 3. Jaundice (hyperbilirubinaemia), although a common benign occurrence in the first week of life, can sometimes progress to critical levels 4.…”
Section: Introductionmentioning
confidence: 99%
“…The present findings indicate that naturally delivered neonates were more likely to have jaundice than those born via cesarean section. Previous studies have shown that the risk of jaundice increases in children delivered via cesarean section [ 5 ]. Similar to our study, Bulbul et al [ 23 ] reported a statistically significant correlation between the severity of jaundice and mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Jaundice itself is not a disease but rather a symptom or sign of a disease [ 5 ]. Many conditions may clinically present as prolonged neonatal jaundice, including neonatal hepatitis and extrahepatic biliary atresia.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that the mean age of the mother was 26.5 years and the mean birth weight of the neonates was 3.15 kgs and mean gestational age was 38.5 weeks. 25…”
Section: Distribution Of Sample Characteristics (Neonatal Factors)mentioning
confidence: 99%